Combination of left ventricular reverse remodeling and brain natriuretic peptide level at one year after cardiac resynchronization therapy predicts long-term clinical outcome - Roubicek, Tomas; Stros, Jan; Kucera, Pavel; Nedbal, Pavel; Cerny, Jan; Polasek, Rostislav; Wichterle, Dan (PloS one, 2019)
INTRODUCTION: The aim of this study was to investigate the predictors of long-term clinical outcome of heart failure (HF) patients who survived first year after initiation of cardiac resynchronization therapy (CRT). METHODS: This was a single-center observational cohort study of CRT patients implanted because of symptomatic HF with reduced ejection fraction between 2005 and 2013. Left ventricle (LV) diameters and ejection fraction, New York Heart Association (NYHA) class, and level of N-terminal fragment of pro-brain natriuretic peptide (NT-proBNP) were assessed at baseline and 12 months after CRT implantation. Their predictive power for long-term HF hospitalization and mortality, and cardiac and all-cause mortality was investigated. RESULTS: A total of 315 patients with left bundle branch block or intraventricular conduction delay who survived >1 year after CRT implantation were analyzed in the current study. During a follow-up period of 4.8±2.1 years from CRT implantation, 35.2% patients died from cardiac (19.3%) or non-cardiac (15.9%) causes. Post-CRT LV ejection fraction and LV end-systolic diameter (either 12-month value or the change from baseline) were equally predictive for clinical events. For NT-proBNP, however, the 12-month level was a stronger predictor than the change from baseline. Both reverse LV remodeling and 12-month level of NT-proBNP were independent and comparable predictors of CRT-related clinical outcome, while NT-proBNP response had the strongest association with all-cause mortality. When post-CRT relative change of LV end-systolic diameter and 12-month level of NT-proBNP (dichotomized at -12.3% and 1230 ng/L, respectively) were combined, subgroups of very-high and very-low risk patients were identified. CONCLUSION: The level of NT-proBNP and reverse LV remodeling at one year after CRT are independent and complementary predictors of future clinical events. Their combination may help to improve the risk stratification of CRT patients.
Keywords: ROC Curve; Humans; srdeční resynchronizační terapie; Heart Failure; srdeční selhání; lidé středního věku; Ventricular Remodeling; natriuretický peptid typu B; funkční vyšetření srdce; Postoperative Period; Female; Aged; výsledek terapie; senioři; lidé; Biomarkers; Cardiac Resynchronization Therapy; časové faktory; biologické markery; ženské pohlaví; Male; Middle Aged; prognóza; Treatment Outcome; Heart Function Tests; Natriuretic Peptide, Brain; ROC křivka; mužské pohlaví; pooperační období; remodelace komor; Time Factors; Prognosis